Oral Tradition Nanga-Nanga in Simeulue Island - TASNIM LUBIS (IPMI Publisher, 2019)
Oral tradition appears in many forms such as pantoons, poetry, songs, plays, and pantoon. Some of them are sung in order to make the performer easier to memorize the lyric. In Simeulue island, Aceh province Indonesia, several oral tradition namely nandong, nanga-nanga, and nafi-nafi are performed through songs. This study focus on describing the meaning of nanga-nanga. It was described through meaning as representative mental and meaning as enaction which is explained by Foley (1997). The data were video-audio recording of nanga-nanga, interview, and observation. The result of study showed that nanga-nanga was performed to express feeling through a story. The meaning of nanga-nanga is the pouring of one’s heart. The performer sung nanga-nanga more to entertain him/herself.